How to determine a therapeutic reference range for a psychotropic drug systematically?: Recommendations of the TDM task force of the AGNP - Hart, Xenia Marlene; Amann, Friederike; Baumann, Pierre; Havemann-Reinecke, Ursula; Schoretsanitis, Georgios; Steimer, Werner; Unterecker, Stefan; Zernig, Gerald; Gründer, Gerhard; Hiemke, Christoph (Therapeutic drug monitoring, 2025)
Background: - Therapeutic drug monitoring (TDM) is essential for controlling pharmacogenetic and pharmacokinetic variations and for optimizing pharmacotherapy. However, its value is often underestimated because of nonsystematic recommendations for target ranges in the literature. The purpose of this study was to emphasize transparency and systematization in the forthcoming Updates to the Arbeitsgemeinschaft für Neuropsychopharmakologie und Pharmakopsychiatrie (AGNP)-TDM Consensus Guidelines. - Methods: - Here, a stepwise method for determining therapeutic reference ranges (TRRs) in psychiatry is introduced. By using various data types, a multidimensional approach for establishing a range is presented. The data types were classified based on how effectively they supported the target ranges. This method was demonstrated for 3 drugs commonly used in psychiatry (aripiprazole, olanzapine, and escitalopram). - Results: - Despite the methodological shortcomings in published concentration-effect studies, the approach used here enabled the determination of reference ranges by combining multiple types of data. The lower limit of the TRR is ideally derived from studies that link blood drug concentrations to clinical effectiveness, particularly symptom-specific responses, after fixed-dose treatment. The upper limit depends on the concentrations associated with adverse reactions or maximal response. Thresholds can be estimated using receiver operating characteristic analyses. Preliminary thresholds were derived from responder concentration data or from expected drug concentrations under approved doses. Positron emission tomography studies were used to further validate these ranges. - Conclusions: - This study proposed a new standard for determining the TRR of psychotropic drugs, thereby enhancing their clinical utility and validity. Adjusting blood levels to these ranges should improve response rates and medication tolerance.